2022
DOI: 10.1186/s12935-022-02674-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a ferroptosis-related five-lncRNA signature for predicting prognosis and immune response in thyroid carcinoma

Abstract: Background Thyroid carcinoma (THCA) is the most common endocrine-related malignant tumor. Despite the good prognosis, some THCA patients may deteriorate into more aggressive diseases, leading to poor survival. This may be alleviated by developing a novel model to predict the risk of THCA, including recurrence and survival. Ferroptosis is an iron-dependent, oxidative, non-apoptotic form of cell death initially described in mammalian cells, and plays an important role in various cancers. To explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In recent years, several prognostic models based on autophagy-related genes 21 , ferroptosis-related genes 22 , cuproptosis-related genes 23 , pyroptosis-related genes 24 have been constructed to predict the prognosis of different cancers. Not only mRNAs but also lncRNAs had been used to establish prognostic models for predicting prognosis 25 28 . Disulfidptosis is a novel type of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several prognostic models based on autophagy-related genes 21 , ferroptosis-related genes 22 , cuproptosis-related genes 23 , pyroptosis-related genes 24 have been constructed to predict the prognosis of different cancers. Not only mRNAs but also lncRNAs had been used to establish prognostic models for predicting prognosis 25 28 . Disulfidptosis is a novel type of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…A calibration curve was used to test the agreement between the actual results and model predictions according to the Hosmer–Lemeshow test. To compare the accuracy, we calculated the consistency index (c-index) and restricted mean survival (RMS) of the published models ( Guo et al, 2022 ; Qin et al, 2022 ; Ding et al, 2022 ; Liu et al, 2022 ; Shan et al, 2022 ) and the model we developed.…”
Section: Methodsmentioning
confidence: 99%
“… Guo et al (2022) revealed that a model composed of seven prognostic lncRNAs of papillary thyroid cancer (PTC). Qin et al (2022) validated a signature supported by four Ferroptosis-related lncRNAs as predictive markers for TC. Numerous studies have shown that lncRNAs influence TC prognosis, which means that we could develop a more accurate TC biomarker based on lncRNAs.…”
Section: Introductionmentioning
confidence: 93%
“…Cancer immunotherapy, such as anti-PDL1-mediated tumor immunotherapy, can downregulate SLC7A11 expression to trigger ferritin responses in cancer cells. Combination treatment with an anti-PDL1 antibody and a ferroptosis inducer also showed synergistic anticancer effects in a mouse model (Stockwell and Jiang, 2019;Qin et al, 2022). The activator of ferroptosis strengthens the immune microenvironment link between ferroptosis and cancer (Yang et al, 2021b).…”
Section: Ferroptosis In Cancersmentioning
confidence: 99%